Reforma al art. 585 del código del trabajo, para que el juez cumpla con las garantías para el normal desenvolvimiento de los principios procesales en las audiencias laborales - Morocho Piedra, Luis Xavier (2014)
The thesis developed concerns "Reform Article 585 of the Labor Code, for the Judge meets the guarantees for the normal development of the procedural principles in Labor Hearings" is indispensable for analysis and input in reviewing judgments work shows that there is infringement of the rights of workers when the employer through the pleadings seeking counsel presents a series of steps in the trial, in order to delay the judicial process; thus exceeds the time limit within which it must have completed litigation and workers' rights have been ensured. However, there lawsuits pending which has spread from normal, violating law and putting aside the non-application of principles of due process guaranteed by the Constitution of the Republic of Ecuador as they are; procedural fairness, promptness contradiction primacy of reality is doubt, operator, among others. The theoretical, legal and doctrinal collection, the study of specific cases, the use of surveys and interviews yielded widely recognized criteria clear and precise basis of literature, which contributed to the verification of the objectives and the testing of the hypothesis regarding this practice; both the Constitution of the Republic of Ecuador, like other labor laws criminalizing the rights of workers, but the judges who must ensure strict compliance with constitutional principles.